2015
DOI: 10.1182/blood-2014-09-600411
|View full text |Cite
|
Sign up to set email alerts
|

Eculizumab reduces complement activation, inflammation, endothelial damage, thrombosis, and renal injury markers in aHUS

Abstract: • This exploratory study describes the effect of eculizumab on multiple physiologic pathways affected by complement dysregulation in aHUS.• The results highlight the importance of sustained terminal complement blockade, even in patients with improved clinical laboratory values.Atypical hemolytic uremic syndrome (aHUS) is a genetic, life-threatening disease characterized by uncontrolled complement activation, systemic thrombotic microangiopathy (TMA), and vital organ damage. We evaluated the effect of terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(152 citation statements)
references
References 81 publications
5
137
0
9
Order By: Relevance
“…The significantly increased levels of C5a and soluble C5b-9 (sC5b-9), markers of terminal complement activation, have been identified in the acute phase of aHUS compared with TTP or healthy controls [52,53]. Moreover, urine C5a, sC5b-9, and alternative pathway activation marker Ba are elevated in acute phase of aHUS, and these markers are decreased by eculizumab administration, with the exception of Ba [54]. However, Noris et al has reported that plasma C5a and sC5b-9 were not suitable markers for diagnosing aHUS, because these values were normal in 9 out of 19 cases even during the acute phase [55].…”
Section: Complement Assessment In Ahusmentioning
confidence: 96%
“…The significantly increased levels of C5a and soluble C5b-9 (sC5b-9), markers of terminal complement activation, have been identified in the acute phase of aHUS compared with TTP or healthy controls [52,53]. Moreover, urine C5a, sC5b-9, and alternative pathway activation marker Ba are elevated in acute phase of aHUS, and these markers are decreased by eculizumab administration, with the exception of Ba [54]. However, Noris et al has reported that plasma C5a and sC5b-9 were not suitable markers for diagnosing aHUS, because these values were normal in 9 out of 19 cases even during the acute phase [55].…”
Section: Complement Assessment In Ahusmentioning
confidence: 96%
“…Los más frecuentes son los de tipo neurológico (48%), incluyendo irritabilidad, somnolencia, confusión, convulsiones, encefalopatía, accidente cerebrovascular, hemiparesias, hemiplejia o coma [12][13][14] , como ocurrió con esta paciente. El infarto agudo de miocardio se ha descrito hasta en un 3% de los pacientes con SHUa, pudiéndose relacionar con muerte súbita 12,15 . La variabilidad de la sintomatología dificulta el diagnóstico diferencial con otras causas de MAT.…”
Section: Patogeniaunclassified
“…A diferencia del SHU que se describió previamente, la trombosis intravascular en la PTT es consecuencia de una deficiencia severa de la actividad de la metaloproteasa ADAMST13, una enzima plasmática encargada de fragmentar los multímeros ultra largos de factor von Willebrand 15 . Actualmente, una deficiencia severa adquirida o congénita de ADAMTS13 (<5-10%) confirma el diagnóstico de Púrpura Trombocitopénica Trombótica (PTT).…”
Section: Diagnósticounclassified
See 2 more Smart Citations